Digital customer experience and social media marketing on purchase intention - Nurfaizal, Yusmedi; Hafshah, Luqyana Nida; Nafisa, Fairuzavina Kafka; Barros, Agapito (Manajemen Komunikasi, 2026)
Background: The development of digital technology changed consumer interaction patterns among students as the generation who uses online platforms to buy branded products. They use online media to get information as well as to do buying transactions. In the digital marketing, intensity of interactions in the digital form increases and gives impacts to online experiences; therefore communication on social media regarding purchase intentions becomes more important. Purpose: We examined some influences of digital customer experiences and social media marketing on formation of buying intentions. We also looked at the role of perceiving value as one mediate variable and trust as moderate variable. Methods: We used quantitative survey with 200 undergraduate students from three universities in Purwokerto, Indonesia: Universitas Jenderal Soedirman, Universitas Muhammadiyah Purwokerto, and Universitas Amikom Purwokerto. Use purposive sampling technique, with citeria must be active social media users and having experiences related to online shopping. To perform data analysis, we used Partial Least Squaes Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 to generate measure and structure models. Results: Digital customer experience and social media marketing significantly rise perceived value and directly strengthen student intention to purchase. Perceived value was a key factor effecting on digital interactions on decision to buy. Trust showed strong relationships between perceived value as well as purchase intentions, indicating that higher levels of trust in digital platforms can grow consumers’ intent of making a buying. Conclusion: In order to increase perceived value and trust among young consumers, some businesses need to create interestingly and interactively digital experiences and to make credible communication on social media. Implications: As digital marketing literature grows, we offer real implications for organizations especially students in online market.